Lingonberry (Vaccinium vitis-idaea L.) Fruit as a Source of Bioactive Compounds with Health-Promoting Effects—A Review - Kowalska, Katarzyna (International journal of molecular sciences, 2021)
Berries, especially members of the Ericaceae family, are among the best dietary sources of bioactive compounds with beneficial health effects. The most popular berries are in the genus Vaccinium, such as bilberry (Vaccinium myrtillus), cranberry (Vaccinium macrocarpon, V. oxycoccos), and blueberry (Vaccinium corymbosum). Lingonberry (Vaccinium vitis-idaea) is less prevalent in the daily human diet because they are collected from the wild, and plant breeding of lingonberry is still on a small scale. Lingonberries are classed as “superfruits” with the highest content of antioxidants among berries and a broad range of health-promoting effects. Many studies showed various beneficial effects of lingonberries, such as anti-inflammatory, antioxidant, and anticancer activities. Lingonberries have been shown to prevent low-grade inflammation and diet-induced obesity in diabetic animals. Moreover, lingonberry intake has been associated with a beneficial effect on preventing and treating brain aging and neurodegenerative disorders. The consumption of berries and their health-promoting activity is a subject receiving a great deal of attention. Many studies investigated the natural compounds found in berries to combat diseases and promote healthy aging. This article’s scope is to indicate the potential beneficial effect of lingonberry consumption on health, to promote well-being and longevity.